A gestão da inserção de tecnologia e inovação em empresas construtoras: um mapeamento sistemático de literatura - Barbosa, Ivan Carlos Alves; Granja, Ariovaldo Denis; Olivieri, Hylton (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The construction industry is a major driver of economies. In Brazil, this industry is strongly dominated by the use of conventional construction methods by contractors, which, in general, employ low-skilled labor. On the one hand, with the increasing development of the housing market in recent years, the construction companies began to analyze the feasibility of the insertion of innovative construction systems, coupled with the need to increase competitiveness and to promote cost reductions efforts. But on the other hand, the implementation of these systems faces barriers such as cultural factors and lack of advice on how to manage this process properly. Additionally, the insertion of these systems is usually focused on short-term gains, meaning the neglect of aspects of the required integrated management related to their implementation. In this sense, there is an opportunity to explore how innovative technological systems should be inserted by construction companies. The research presents a Systematic Mapping Study (SMS) focused on the management of technology insertion and innovation in construction companies. The results suggest that the analyzed documents are predominantly conceptual, or they mix concepts with techniques, and the theme is encouraging researches for more than thirty years, with a increasing intensity in the last ten years